(untitled) (Research, Society and Development, 2021)
In 2050, 70% of the world population will live in cities, putting pressure on management to become intelligent and stakeholders gain relevance and interest as an object of study, starting to dispute the protagonism in these territories. We have’t identified studies that recognize these stakeholders in smart cities. The objective was to identify them, as well as their attributes and their salience. We performed a systematic literature review and obtained 82 final documents. As a result, Civil society was the most cited stakeholder, followed by industries / companies, followed by governments and, finally, by academia / universities. The results, both by geographic region of study and by the academic background of the authors, refer to the same result. We did not identify any mention of the salience and attributes of stakeholders in smart cities, indicating a scientific gap to be studied in the future. Teaching and research was the least significant segment among the stakeholders, indicating the need to include this group as active protagonists in this process. We conclude that civil society needs to be effectively involved in these smart cities’ initiatives, after all, these are the main shareholders of these cities.